2015
DOI: 10.2217/fon.14.142
|View full text |Cite
|
Sign up to set email alerts
|

Environmental (nongenetic) factors in gynecological cancers: update and future perspectives

Abstract: Globally, gynecological cancers comprise three of the seven most common female cancers and are responsible for more than 1,000,000 new cases and 500,000 deaths annually. This review summarizes current knowledge regarding the role of environmental factors in gynecological cancer etiology and survival, focusing on those that are potentially amenable to intervention. Strong associations with use of exogenous hormones are countered by opposing risks of breast cancer, thus current hormonal preparations are not an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 85 publications
2
26
0
2
Order By: Relevance
“…This latter result can also be deduced from (15) for narrow resonances with long relaxation times. Namely, for small τ/T * + 2k , the series expansion for exp(−τ/T * + 2k ) yields…”
Section: Modes Of the Component Spectrasupporting
confidence: 58%
See 2 more Smart Citations
“…This latter result can also be deduced from (15) for narrow resonances with long relaxation times. Namely, for small τ/T * + 2k , the series expansion for exp(−τ/T * + 2k ) yields…”
Section: Modes Of the Component Spectrasupporting
confidence: 58%
“…As stated earlier [see also (15) and (16)], it should be emphasized that peaks heights in the absorption mode of a conventional Lorentzian lineshape are given by (…”
Section: Separation Of the Spurious From The Genuine Resonances In Thmentioning
confidence: 82%
See 1 more Smart Citation
“…Due to the changes to the human lifestyle, the occurrence of reproductive-, diet-and hormone-associated types of cancer is increasing (17). Accumulating evidence has revealed that miRs participate in tumorigenesis, tumor development, drug resistance and other pathological processes of cancer (18).…”
Section: Discussionmentioning
confidence: 99%
“…• метаболический синдром: избыточная масса тела и ожирение, нарушение метаболизма глю-козы, низкая физическая активность; • отягощенный злокачественными опухолями семейный анамнез [7,8]. Представленные факторы риска РЯ согласуются с данными о том, что ЗН яичников в большинстве слу-чаев гормонозависимы.…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified